SATISFACTION ANALYSIS OF ROSE CULTIVATORS TOWARDS INSECTICIDE X (CASE STUDY AT GUNUNGSARI VILLAGE, BUMIAJI DISTRICT, BATU CITY) - Matthew Howard Lambert; Ratya Anindita; Condro Puspo Nugroho (Socio-Economics/Agribusiness Department, 2018)
The objective of this research is to describes the reasoning of continuous buying decision and to analyze consumer satisfaction of roses cultivators towards insecticides X. The method research are quantitative descriptive, Importance-Performance Analysis (IPA), and Customer Satisfaction Index (CSI). Five process of buying decision such as needs recognition, information seeking, alternative evaluation, purchase decision, and post-purchase behavior also the three main indicators such as sociocultural environment, consumer psychology, and marketing efforts are used to describes the buying decision. Eight indicators of a product such as performance, features, conformity, durability, serviceability, aesthetics, and perceived quality are used to measure the consumers satisfaction. The samples of 33 roses cultivators are used. The result of buying decision describes that the influence indicators according to main indicators of buying decision are products association, information sources, shop selection, and future buying possibilities.The result of IPA method are 85,9 percent of consumers suitability level therefore needs to be improved. The result of CSI are 60,21 percent of satisfaction level and included in average satisfied category.